Reflexiones en torno al establecimiento del poderío cartaginés en Hispania - Barceló, Pedro (Millars. Espai i Història, 2018)
This contribution analyses the actions of the Carthaginians in the south and the southwest of Iberia of which the Barcides were the protagonists. Because of a new interpretation of the literary sources ¡n connection with the archeological evidence is concluded that the river mentioned in the treaty of Asdrubal cannot be the river Ebro. There is a great probability that the river Segura was the boarder line of the Carthaginian influence in Iberia. This leads us to a better comprehension of the political situation in Iberia before the outbreak of the Second Punic War.